The Unity of Mankind and the Conversation of Civilizations : Reflections on the Basis of Eric Voegelin's The Ecumenic Age - Bark, Axel,; Bergbauer, Harald, (Eric Voegelin Studies: Yearbook ;, 2025)
The book focuses on Eric Voegelin's work "The Ecumenic Age", which contains an original interpretation of universal history (I). In addition to analyses of the ecumenic age, the volume contains a series of further articles on political theory and the philosophy of history (II), as well as some concluding reviews of new publications and classic works (III).